PERMAINAN TRADISIONAL KAULINAN BARUDAK UNTUK MENGEMBANGKAN KEMAMPUAN MENGELOLA EMOSI DIRI SENDIRI ANAK USIA DINI - Mulyadiprana, Ahmad; Ganda, Nana; WS, Rustono (Universitas Pendidikan Indonesia (UPI), 2017)
This research is based on the facts in the field regarding the process of achieving early childhood education that is not optimal. Eeducational attainment is about to manage sel emotion of early childhood. The traditional games